Implementation of Flexible Work Arrangements for Sustainable Development - Čiarnienė, Ramunė; Vienažindienė, Milita; Adamonienė, Rūta (European Journal of Sustainable Development, 2018)
Rapid globalization, the Internet-enabled on-demand economy, changing demographics, dynamism and flexibility in the workforce are redefining the landscape of work and inevitably lead to the changes in work arrangements. Flexible work arrangement (FWA) can be defined as a set of benefits provided by employer that lets employees to control over when and where they work outside of the standard arrangement. Although the concept of flexible work arrangements (FWAs) is quite widely analysed by scientific community during past decades, there is a lack of knowledge exploring the impact of flexible work practices on sustainable development. The purpose of this paper is to examine how flexible work arrangements can contribute to sustainable development at different levels of abstraction. Research methodology includes comparative analysis and synthesis of scientific literature, modelling, and empirical research in the form of survey and semi-structured interview. Research revealed that FWAs, when implemented with care and preparation, have a positive influence on sustainability at different levels of abstraction: individual level, company level, and society level. Benefits of flexible work practices turn up through three interconnected domains: economic, environmental, and social. Keywords: flexible work arrangements, sustainability, sustainable development, employees, organization